2020
DOI: 10.1111/aor.13784
|View full text |Cite
|
Sign up to set email alerts
|

Probing expert opinions on the future of kidney replacement therapies

Abstract: Patients with kidney failure can only survive with some form of kidney replacement (transplant or dialysis). Unfortunately, innovations in kidney replacement therapy lag behind many other medical fields. This study compiles expert opinions on candidate technologies for future kidney replacement therapies. A worldwide web‐based survey was conducted with 1566 responding experts, identified from scientific publications on kidney (renal) replacement therapy, indexed in the Web of Science Core Collection (period 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…From 25,000 invited researchers, 1030 agreed to participate in the study—after excluding 66 respondents who did not consent to participate. This number gave us a response rate of 4.12%, which is compatible to the response rate found in other future-oriented studies that used the same survey method [ 52 , 53 , 57 , 58 ]. Of these 1030 researchers, 26.02% reported having a high knowledge of AI in cancer care, while 42.72% and 28.93% reported having good and some knowledge, respectively.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…From 25,000 invited researchers, 1030 agreed to participate in the study—after excluding 66 respondents who did not consent to participate. This number gave us a response rate of 4.12%, which is compatible to the response rate found in other future-oriented studies that used the same survey method [ 52 , 53 , 57 , 58 ]. Of these 1030 researchers, 26.02% reported having a high knowledge of AI in cancer care, while 42.72% and 28.93% reported having good and some knowledge, respectively.…”
Section: Resultssupporting
confidence: 86%
“…The last part covered five demographic questions, where the respondents could report their academic degree, professional occupation, institutional affiliation, professional experience, and region where they live. The demographics of the respondents do not influence the results of this type of study [ 51 , 52 , 53 , 54 ]. They were used to present an overview of the study participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques may improve the health state of patients by continuous removal of uremic toxins, increased mobility, and hence improved QoL besides low‐cost options. In this regard, an extensive global expert survey revealed that major breakthroughs are expected to be most likely by wearable artificial kidneys and implantable artificial kidneys 129 . However, also the wearable PD concept needs to be further miniaturized.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, an extensive global expert survey revealed that major breakthroughs are expected to be most likely by wearable artificial kidneys and implantable artificial kidneys. 129 However, also the wearable PD concept needs to be further miniaturized. A problem of PD is the potential microbiological contamination of the intestine and the subcutaneous access channel of the catheters.…”
Section: Discussionmentioning
confidence: 99%